2011
DOI: 10.1007/s10658-011-9896-x
|View full text |Cite
|
Sign up to set email alerts
|

Detection and prediction of post harvest carrot diseases

Abstract: Specific PCR primers were developed for identifying two post harvest pathogens, Mycocentrospora acerina and Fibularhizoctonia carotae, which cause liquorice rot and crater rot respectively, during prolonged low temperature storage of carrots. The methods allow routine detection of less than 0.3 pg of M. acerina DNA and less than 0.03 pg F. carotae DNA, even in the presence of large excess of plant or soil DNA. Standard PCR and quantitative PCR gave similar results and either method could be used in a practical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…are considered to cause pits and cavities on parsnip (Channon & Thomson, 1981) and potato (Choiseul et al, 2006), they may also have a role in the symptom development on carrot. Alternaria radicina , Athelia arachnoidea or Rhexocercosporidium carotae species, found causing pit symptoms in carrot in other countries in Europe (Årsvoll, 1969; Hermansen et al, 2012; Kastelein et al, 2007; Snowdon, 1992), were not detected in the samples from Finland. No symptoms characteristic of carrot infection by Berkeleyomyces spp.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…are considered to cause pits and cavities on parsnip (Channon & Thomson, 1981) and potato (Choiseul et al, 2006), they may also have a role in the symptom development on carrot. Alternaria radicina , Athelia arachnoidea or Rhexocercosporidium carotae species, found causing pit symptoms in carrot in other countries in Europe (Årsvoll, 1969; Hermansen et al, 2012; Kastelein et al, 2007; Snowdon, 1992), were not detected in the samples from Finland. No symptoms characteristic of carrot infection by Berkeleyomyces spp.…”
Section: Discussionmentioning
confidence: 99%
“…The DNA samples were tested for the presence of M. acerina, F. avenaceum and B. cinerea by single PCR reactions using speciesspecific primers. The primers were KLO15F (CGGTCGGACTCCATT CAAAC) and KLO20R (GCTCCGAAGCAAGTACGCCG) for M. acerina (Hermansen et al, 2012), FA-F1 (AACATACCTTAATGTTGCCTCGG) and FA-R1 (ATCCCCAACACCAAACCCGAG) for F. avenaceum (Mishra et al, 2003), and Bc-F (CAGGAAACACTTTTGGGGATA) and Bc-R (GAGGGACAAGAAAATCGACTAA) for B. cinerea (Fan et al, 2015). The sizes of the expected PCR products were 314 bp, The PCR products were analysed by electrophoresis on 1.5% agarose gels in Tris-borate-EDTA buffer.…”
Section: Identification By Molecular Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified that the brown balls in egg piles of R. labralis were the sclerotia of Fibulorhizoctonia sp. Fibulorhizoctonia is a genus of fungi in the Atheliaceae family, and three widespread species have been named, F. carotae , F. centrifuga and F. psychrophila , which were consistently isolated from decayed fruits, vegetables and wooden storage bins 1,7,8 . Most fungi produce some type of durable microscopic structure such as a spore that is important for dispersal and/or survival under adverse conditions.…”
Section: Discussionmentioning
confidence: 99%